Engaging Through Games: An Analysis of Gamification as an Intervention in Opinion Research - Klein, Amanda; Oliveira, Kayque; Caetano, Bárbara Pimenta; Paula, Melise Veiga (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2024: Anais do XX Simpósio Brasileiro de Sistemas de Informação, 2024)
Context: A resource widely used in various areas such as government, education, and the market to expand knowledge is Opinion Survey. The technology can improve the ability to collect, store, and analyze data generated in an opinion survey. On the other hand, in many contexts, the opinion survey is used to expand knowledge about different aspects of the development of information systems. Problem: However, a lack of engagement in opinion surveys can compromise the results achieved, reducing the data collected quality. This problem to may interfere on opinion surveys due to the lack of representation. Proposed Solution: This research aimed to explore how gamification can serve as a motivational factor to stimulate this engagement. Therefore, we are developing a gamificated tool to support opinion research. IS Theory: Considering the prescriptive nature of this research, whose focus is to build an artifact to support opinion research, DSR has been considered as an approach to support the development of the solution in an attempt to mitigate problems related to engagement and generate new knowledge to help clarify our understanding of this area of research. The develepopment these artifacts at an abstract level means that they can be operationalized in a number of other unstudied contexts, thus increasing the external validity of the research. Methodology: The methodology was established based on the epistemological paradigm of Design Science Research (DSR), employed for an initial investigation that resulted in the development of two artifacts: the Collaborative Engagement Model (CEM) and the "Opina Aí" application. Summary of Results: The artifacts were assessed in an experiment comparing the gamified version with the non-gamified one, analyzing application usage and usability. While the results regarding the impact of gamification on engagement were inconclusive, valuable insights were gained. Contributions and Impact in the IS Field: This study expands knowledge in the area of gamification, and may provide new perspectives for future studies in contexts where participation is exercised collaboratively, using information systems.